2020
DOI: 10.3390/ma13020258
|View full text |Cite
|
Sign up to set email alerts
|

Fused Deposition Modeling of Poly (lactic acid)/Macadamia Composites—Thermal, Mechanical Properties and Scaffolds

Abstract: In this work Macadamia nutshell (MS) was used as filler in fused deposition modeling (FDM) of Poly (lactic acid) (PLA) composites filaments. Composites containing MS both treated and untreated with alkali and silane were investigated by means of Fourier transform infrared spectroscopy (FTIR), X-Ray diffraction (XRD), Thermogravimetry (TG), scanning electron microscopy (SEM). The results showed that the treated MS composites had better thermal stability. Furthermore, compression tests were carried out. The PLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…One study concluded that a blend of polycarbonate referred to as a bio-based polycarbonate had a slightly higher strength of 65 MPa and significantly higher elastic modulus of 2100 MPa than a polycarbonate manufactured using fossil fuels with 62 MPa strength and 1500 MPa elastic modulus [ 35 ]. Polyether ether ketone (PEEK) and polylactic acid (PLA) are commonly used biocompatible materials with relatively high mechanical strength and stiffness among polymers, and are also manufacturable with fused deposition modeling [ 37 , 38 ]. PEEK is generally the more expensive of the two materials with an elastic modulus up to 4100 MPa, while PLA has an elastic modulus of 4400 MPa; both are the highest values among the surveyed Table 1 materials.…”
Section: Materials Capabilitiesmentioning
confidence: 99%
“…One study concluded that a blend of polycarbonate referred to as a bio-based polycarbonate had a slightly higher strength of 65 MPa and significantly higher elastic modulus of 2100 MPa than a polycarbonate manufactured using fossil fuels with 62 MPa strength and 1500 MPa elastic modulus [ 35 ]. Polyether ether ketone (PEEK) and polylactic acid (PLA) are commonly used biocompatible materials with relatively high mechanical strength and stiffness among polymers, and are also manufacturable with fused deposition modeling [ 37 , 38 ]. PEEK is generally the more expensive of the two materials with an elastic modulus up to 4100 MPa, while PLA has an elastic modulus of 4400 MPa; both are the highest values among the surveyed Table 1 materials.…”
Section: Materials Capabilitiesmentioning
confidence: 99%
“… ( a ) The maximum tensile strength with fiber wt.% [ 30 , 34 , 35 , 38 , 39 , 40 , 41 , 42 , 44 , 47 , 51 , 62 ]. ( b ) the maximum tensile strength with fiber wt.% [ 36 , 37 , 52 , 54 , 55 , 63 , 64 , 66 , 68 , 70 , 71 , 72 ].…”
Section: Figurementioning
confidence: 99%
“…In this context, the polymer composites that use macadamia nutshell as reinforcement have been standing out. This nut had its production and, consequently, the waste disposal, increased both in Australia and in the southwest region of Brazil 6–10 …”
Section: Introductionmentioning
confidence: 99%